Structural studies of the nucleus-like assembly of jumbo bacteriophage 201φ2-1 - Liu, Zhe; Xiang, Ye (Frontiers in Microbiology, 2023)
The jumbo phages encode proteins that assemble to form a nucleus-like compartment in infected cells. Here we report the cryo-EM structure and biochemistry characterization of gp105, a protein that is encoded by the jumbo phage 201φ2-1 and is involved in the formation of the nucleus-like compartment in phage 201φ2-1 infected Pseudomonas chlororaphis. We found that, although most gp105 molecules are in the monomeric state in solution, a small portion of gp105 assemble to form large sheet-like assemblies and small cube-like particles. Reconstruction of the cube-like particles showed that the particle consists of 6 flat head-to-tail tetramers arranged into an octahedral cube. The four molecules at the contact interface of two head-to-tail tetramers are 2-fold symmetry-related and constitute a concave tetramer. Further reconstructions without applying symmetry showed that molecules in the particles around the distal ends of a 3-fold axis are highly dynamic and have the tendency to open up the assembly. Local classifications and refinements of the concave tetramers in the cube-like particle resulted in a map of the concave tetramer at a resolution of 4.09 Å. Structural analysis of the concave tetramer indicates that the N and C terminal fragments of gp105 are important for mediating the intermolecular interactions, which was further confirmed by mutagenesis studies. Biochemistry assays showed that, in solution, the cube-like particles of gp105 are liable to either disassemble to form the monomers or recruit more molecules to form the high molecular weight lattice-like assembly. We also found that monomeric gp105s can self-assemble to form large sheet-like assemblies in vitro, and the assembly of gp105 in vitro is a reversible dynamic process and temperature-dependent. Taken together, our results revealed the dynamic assembly of gp105, which helps to understand the development and function of the nucleus-like compartment assembled by phage-encoded proteins.